Fatwa tentang Pembiayaan Pengurusan Dana Haji dan Status Dana Calon Haji Daftar Tunggu - Mubarok, Jaih; Hasanuddin, M (Al-Iqtishad: Journal of Islamic Economics, 2013)
There are different fatwa between DSN-MUI and council Hisbah Persis relating to financing Hajj arrangements and the status of waiting list Hajj candidates. However, in substance, the DSN MUI fatwa and is not in contradiction with the Council Hisbah Persis because both fatwas forbid bailout that taalluq between qardh with ujrah. To reach istithaah fi ada al-hajj, a person is prohibited to invade other parties that is istithaah, MUI fatwa requires that recipients must pay off the fund before the hajj realized. BPIH funds is belong to depositors and is placed at Islamic banks in form of saving or deposit belonging to depositor.DOI: 10.15408/aiq.v5i1.2107